Conservative Chemotherapy in Gestational Trophoblastic Disease: Experience With Etoposide, Methotrexate, and Dactinomycin Chemotherapy. Issue 4 (May 2016) - Byun, Seung Won; Park, Tae Chul; Bae, Seog Nyeon
Abstract : Objective: The goal of this study was to evaluate the efficacy, toxicity, and survival of patients in our institution treated by EMA (etoposide, methotrexate [MTX], and dactinomycin) chemotherapy for 3 groups of patients: ones that had low-risk gestational trophoblastic disease (GTD) that was resistant to MTX (group A), those with high-risk GTD (group B), and the group having low-risk GTD but the cancer being metastatic (group C). Methods: The medical records of 58 patients who received EMA chemotherapy in groups A, B, and C in the 2000 to 2012 period at St Mary's Hospital were examined. Clinical characteristics, chemotherapy responses, causes of treatment failure, and cases of drug toxicity were analyzed retrospectively. Results: Treatment with the EMA regimen resulted in primary remission in 52 (96%) of 54 patients and resistance in 2 of the patients (3%). In the resistance group, one belonged to group B and was treated with etoposide, MTX, and actinomycin D with cyclophosphamide and vincristine (EMA-EP) and the other belonged to group A and died of refractory disease. World Health Organization (WHO) grade 4 leukocytopenia and thrombocytopenia with the EMA regimen occurred in 6% and 0.4% of the cycles, respectively; the other toxic effects were acceptable and manageable. Median cycles of EMA chemotherapy during the treatment were 7, 8, and 8 in groups A, B, and C, respectively. There was some reduction in total chemo cycle and toxicity, as compared with a previously reported study using the alternative cyclophosphamide and vincristine regimen. Among the EMA treated patients, 1 patient with a second malignancy of breast cancer was documented. In addition, 5 child births for the treated patients were recorded during the follow-up period of mostly 10 years. Conclusions: The EMA chemotherapy seemed to reduce treatment duration and the relapse rate without increasing the adverse effects in patients with MTX resistance and low-risk GTD, but having confirmed metastatic lesions. Although this study had some limitations regarding the high-risk GTD, our findings will provide a basis for the use of EMA chemotherapy when cyclophosphamide and vincristine is contraindicated due to toxicity.